2019
DOI: 10.1177/0734242x19826327
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of willingness-to-pay for the MSW disposal system by choice experiment approach: A case study of Taiwan

Abstract: In Taiwan, municipal solid waste (MSW) is separated into general, recyclable, and food waste categories. General waste must be packaged into pre-paid trash bags before final disposal. Recyclable items and food waste are collected separately to reduce the costs of using pre-paid trash bags. This study applied a choice experiment approach to evaluate marginal willingness-to-pay (WTP) in different MSW disposal system scenarios. Variables include cleanliness, location for purchasing pre-paid trash bags, frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(43 reference statements)
1
7
0
1
Order By: Relevance
“…Also, Kusturica et al (2020) stated that gender influenced WTP for a pharmaceutical disposal programme in Serbia. However, Chen (2019) found no significant difference between gender in terms of WTP for a solid waste disposal system in Taiwan. Song et al (2016) and Boateng et al (2019) found educational level had a significant effect on WTP for improved solid waste management services in Ghana and Macau, respectively.…”
Section: Socio-demographic Characteristics Of Respondents and Willing...mentioning
confidence: 78%
See 1 more Smart Citation
“…Also, Kusturica et al (2020) stated that gender influenced WTP for a pharmaceutical disposal programme in Serbia. However, Chen (2019) found no significant difference between gender in terms of WTP for a solid waste disposal system in Taiwan. Song et al (2016) and Boateng et al (2019) found educational level had a significant effect on WTP for improved solid waste management services in Ghana and Macau, respectively.…”
Section: Socio-demographic Characteristics Of Respondents and Willing...mentioning
confidence: 78%
“…Many researchers have begun to focus on WTP due to environmental concerns and for healthcare services improvements (Khattak et al, 2009;Afroz & Masud, 2011;Afroz et al, 2013;Aizuddin & Al Junid, 2018;Owusu-Amankwah, 2018;Boateng et al, 2019;Chen, 2019;Kusturica et al, 2020). Aizuddin and Al Junid (2018) explored the WTP for revised government outpatient registration fees for healthcare services among the Malaysian population.…”
Section: Willingness To Pay Literature On Healthcarementioning
confidence: 99%
“…O Pay-As-You-Throw (PAYT) é um dos principais incentivos econômicos utilizadas por países com baixo desempenho na gestão de RSU para reduzir a geração e aumentar a reciclagem (Kling et al, 2016). A título de exemplo, a implementação de PAYT reduziu a geração per capita em mais de 50% (em apenas 1 ano) em algumas cidades Italianas (Bonelli et al, 2016) e aumentou a reciclagem em mais de 30% em Taiwan (Chen, 2019). Entretanto, considera-se pouco provável a sua adesão no Brasil, uma vez que, possui alto custo financeiro em função dos requisitos de controle e fiscalização (Seacat & Boileau, 2018).…”
Section: Resultsunclassified
“…CVM or a choice experiment (CE) is widely utilized in WTP estimates and influence of various factors on WTP [81][82][83]. CE approach generates choice scenarios presented to the participants to make their choices from among the scenarios in a choice set, during the data collection process [81][82][83].…”
Section: Professional Biases In Decision-makingmentioning
confidence: 99%